The Usage of Schoology and Canvas as Media Based Blended Learning - Dewi Yana (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2018)
Lecturers are no longer occupying the single position in conveying knowledge to the digital natives. Hence, they have to adapt the effect of the fourth industrial revolution in the teaching learning process through hybrid learning which combine the face-to-face classroom to the online or offline technology. Thus, this study aims at measuring the students’ learning achievement in studying use kinds of media based blended learning at University of Riau Kepulauan, Batam Indonesia. It was a quasi-experimental method with nonequivalent control group design. The population was all of the sixth semester students with purposive sampling technique. The instrument was in the form of written test which have been validated and reliable previously. The data were measured statistically use T-test. The result exposed that pre-test and post-test marks of the two groups revealed a notable enhancement. It recommends to instructors, or curriculum designer in applying such media based vitual learning to encourage learners’ accomplishment.